Psychological Effects of Viewing News Channels Among Adult Population of Karachi, Pakistan - Komal Madad Ali Daredia; Nosheen Zehra; Shahida Rasheed (ziauddin University, 2024)
Background: News viewing is directly linked to a person's cognitive behavior and hence deeply affects psychological status of the viewer. Live events and deteriorating images affects different aspects of a person's cognition. Stress is one of them which was measured in this study using a Psychological Stress Scale (PSS). Objective: To assess the psychological effects of viewing news channels among adult population of Karachi, Pakistan. Methods: This Cross Sectional study was carried out for a 2 month duration targeting the adult population of Karachi. Total 400 participants were selected through the convenience sampling technique. A pretested and self administered questionnaire was used to collect data. PSS (Psychological Stress Scale) was used to measure stress among study participants. The data was analyzed using SPSS version 20. Results: Of total n=400 participants, 273 (68.3%) used TV as the source of getting news and at the time of watching TV 166 (41.5%) preferred to watch news channels. 115 (28.8%) individuals had lasting effect after watching news of violence and 173 (43.3%) participants were stressed after watching news. Using PSS, 288 (72%) individuals had moderate stress score, 78 (19.8%) had low and 34(8.3%) had high stress score. Conclusion: It was concluded from the research that news is adversely affecting the psychological health Key Words: Psychological Effects, News Channel, Psychological Stress Scale (PSS).